A new species of Apelaunothrips (Thysanoptera: Phlaeothripidae) from India with new synonym of Podothrips sasacola Kurosawa - Tyagi, Kaomud; Singha, Devkant; Chakraborty, Rajasree; Pakrashi, Avas; Kumar, Vikas (Zootaxa, 2020)
The first objective of this paper is to describe a new fungus-feeding species in the Phlaeothripinae genus Apelaunothrips, and to provide a key to the six species of this genus recorded from India. The second objective is to establish a new synonym in the Poaceae-associated genus, Podothrips, based on structural variation observed among recently collected samples from bamboo. The slide-mounted specimens were studied with a Leica Trinocular Microscope (Leica DM-1000) and a Leica software application suite (LAS EZ 2.1.0) was used to make line drawing and photographs.